Modeling of electron beam distribution in electron beam welding. Issue 3 (November 2018) - Seregin, Yu N; Murygin, A V; Laptenok, V D; Tynchenko, V S
Abstract: The results of mathematical simulation of the electron beam distribution during heating of AMG-6 alloy by moving instantaneous energy sources equivalent to a beam in electron-beam welding are presented in the article. The calculations were carried out using the functional developed by the authors. The paper presents the results of calculations and an algorithm for searching for the optimal technological regime of electron beam welding, which can be recommended for designing electron-beam welding technology for new construction materials or for upgrading old process technology. The results of modeling the technological process for welding a 2.4-cm thick plate made of AMG-6 material, which were compared with the experimental data obtained under laboratory conditions, are presented in this paper.